An unlikely partnership? New Zealand–South Korea bilateral cooperation and Antarctic order. (18th January 2021) - Flamm, Patrick
Abstract: While the Antarctic Treaty System intended to keep Antarctica an area of international cooperation and science free from militarisation and international conflict, the region has not been completely shielded from global power transitions, such as decolonisation and the end of the Cold War. Presently, emerging countries from Asia are increasingly willing to invest in polar infrastructure and science on the back of their growing influence in world politics. South Korea has also invested heavily in its Antarctic infrastructure and capabilities recently and has been identified as an actor with economic and political interests that are potentially challenging for the existing Antarctic order. This article first assesses the extent and performance of the growing bilateral cooperation between South Korea and one of its closest partners, New Zealand, a country with strong vested interests in the status quo order. How did the cooperation develop between these two actors with ostensibly diverging interests? This article finds that what may have been a friction–laden relationship, actually developed into a win-win partnership for both countries. The article then moves on to offer an explanation for how this productive relationship was made possible by utilising a mutual socialisation approach that explores socio-structural processes around status accommodation.